Efficacy and safety of acupuncture treatment for idiopathic deafness: a retrospective study - Wen, Chun-li; Zhang, Yong-kang; Zhang, Min; Song, Li-juan; Zhu, Ling-qun; Zhang, Fu-Peng (Frontiers in Neurology, 2025)
ObjectiveThe aim of this study was to observe the clinical efficacy and safety of conventional treatment combined with acupuncture in the treatment of idiopathic deafness.MethodsThis retrospective study enrolled 141 patients with idiopathic deafness hospitalized from January 2018 to December 2019. We compared the patients according to previous therapy (conventional treatment and acupuncture treatment), demographics, type of deafness, pure tone hearing threshold score, concomitant symptoms, adverse events and outcomes.ResultsA total of 141 patients were assigned to a control group (n = 67, with simple routine Western medicine treatment) and an observation group (n = 74, with acupuncture treatment on the basis of Western medicine therapy). The total effective rate was 98.65% in the observation group, compared with 74.63% in the control group (p < 0.001). The tinnitus and vertigo were both improved in both groups, and the observation group was better than the control group (p < 0.05). Adverse reactions occurred in one patient (1.35%) in the observation group and in five patients (7.46%) in the control group (p = 0.085).ConclusionAmong patients with idiopathic deafness who can be treated after the onset of symptoms, the combination of acupuncture and conventional treatment is superior to conventional treatment alone for improving clinical efficacy, reducing concomitant symptoms and not increasing the risk of adverse events.